2018
DOI: 10.1161/strokeaha.118.022330
|View full text |Cite
|
Sign up to set email alerts
|

Focal Cerebral Ischemia and Reperfusion Induce Brain Injury Through α2δ-1–Bound NMDA Receptors

Abstract: Background and Purpose: Glutamate N-methyl-D-aspartate receptors (NMDARs) play a major role in the initiation of ischemic brain damage. However, NMDAR antagonists have no protective effects in stroke patients, possibly because they impair physiological functions of NMDARs. α2δ−1 (encoded by Cacna2d1) is strongly expressed in many brain regions. We determined the contribution of α2δ−1 to NMDAR hyperactivity and brain injury induced by ischemia and reperfusion. Methods: Mice were subjected to 90 min of middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 39 publications
1
63
0
Order By: Relevance
“…Because the C-terminus of a2d-1 is essential for its interaction with NMDARs, we developed a 30-amino-acid peptide (VSGLNPSLWSIFGLQ-FILLWLVSGSRHYLW) mimicking the C-terminal domain of a2d-1 fused with Tat protein (YGRKKRRQRRR) termed as a2d-1Tat peptide. We have shown that a2d-1Tat peptide effectively disrupts the a2d-1-NMDAR interaction in vitro and in vivo Luo et al 2018). Treatment with this a2d-1Tat peptide (1 lM for 30-60 min) completely normalized the increased baseline frequency of mEPSCs in lamina II neurons from paclitaxel-treated rats (n = 10 neurons) to the level seen in vehicle-treated rats ( Fig.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Because the C-terminus of a2d-1 is essential for its interaction with NMDARs, we developed a 30-amino-acid peptide (VSGLNPSLWSIFGLQ-FILLWLVSGSRHYLW) mimicking the C-terminal domain of a2d-1 fused with Tat protein (YGRKKRRQRRR) termed as a2d-1Tat peptide. We have shown that a2d-1Tat peptide effectively disrupts the a2d-1-NMDAR interaction in vitro and in vivo Luo et al 2018). Treatment with this a2d-1Tat peptide (1 lM for 30-60 min) completely normalized the increased baseline frequency of mEPSCs in lamina II neurons from paclitaxel-treated rats (n = 10 neurons) to the level seen in vehicle-treated rats ( Fig.…”
Section: Resultsmentioning
confidence: 70%
“…; Luo et al . ). Treatment with this α2δ‐1Tat peptide (1 μM for 30–60 min) completely normalized the increased baseline frequency of mEPSCs in lamina II neurons from paclitaxel‐treated rats ( n = 10 neurons) to the level seen in vehicle‐treated rats (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The C terminus of α2δ-1 is required for its interaction with NMDA receptors, 23 and a Tat (YGRKKRRQRRR)-fused 30-amino-acid peptide (VSGLNPSLWSIFGLQFILLWLVSGSRHYLW) effectively disrupts the α2δ-1-NMDA receptor interaction in vivo. 23,33 To determine the ability of α2δ-1Tat peptide to disrupt the α2δ-1-NMDA receptor interaction in the spinal cord of morphine-treated rats, we conducted coimmunoprecipitation analyses using membrane extracts of spinal cord tissue sections treated with 1 µM Tat-fused scrambled control peptide (FGLGWQPWSLSFYLVWSGLILSVLHLIRSN) or 1 µM α2δ-1Tat peptide for 30 min. Treatment with α2δ-1Tat peptide significantly reduced the level of the α2δ-1-GluN1 protein complex in the dorsal spinal cord, compared with that treated with the control peptide (P = 0.008, t (10) = 3.331, n = 6 rats/group; fig.…”
Section: Chronic Morphine Treatment Increases the Prevalence Of α2δ-1mentioning
confidence: 99%
“…We used a 30-amino acid peptide (VSGLNPSLWSIFGLQFILLWLVSGSRHYLW) mimick-ing the C-terminal domain of ␣2␦-1, which specifically diminishes the ␣2␦-1-NMDAR interaction (17). Because ␣2␦-1 primarily promotes forward trafficking of intracellular ␣2␦-1bound NMDARs, we fused the peptide to the cell-penetrating peptide Tat (YGRKKRRQRRR), generating ␣2␦-1Tat peptide to disrupt the interaction between ␣2␦-1 and NMDARs (17,35). We have shown that ␣2␦-1Tat peptide has no effect on VGCC currents and the Cav␣1-␣2␦-1 interaction (17,35).…”
Section: ␣2␦-1 Is Critically Required For Tbs-induced Corticostriatalmentioning
confidence: 99%